Lipid metabolic profiling and diagnostic model development for hyperlipidemic acute pancreatitis - Ren, Dongmei; Li, Yong; Zhang, Guangnian; Li, Tiantian; Liu, Zhenglong (Frontiers in Physiology, 2024)
Hyperlipidemic acute pancreatitis (HLAP) is a form of pancreatitis caused by hyperlipidemia, which poses significant diagnostic challenges. This research examined the serum lipid metabolism profiles of HLAP patients compared to a healthy cohort. By employing ultra-performance liquid chromatography-tandem mass spectrometry and orthogonal partial least squares discriminant analysis (OPLS-DA), 393 distinct lipid metabolites were detected, affecting critical metabolic pathways such as fatty acid metabolism, sphingolipid metabolism, and glycerophospholipid metabolism. Using Logistic regression and LASSO regression methods, five specific lipid molecules were identified to create a diagnostic model, achieving an AUC of 1 in the ROC curve, indicating exceptional diagnostic accuracy. These results emphasize the importance of lipid metabolism disturbances in HLAP and suggest these lipid molecules could serve as valuable biomarkers for diagnosing HLAP.